Control cognitivo y su relación con distintas tareas de memoria de trabajo - Manríquez Calderón, Sarahí del Carmen (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Cognitive control (CC) is a process that coordinates mental operations under conditions of uncertainty at perceptual or higher levels controlling what information reaches consciousness for decision-making. Due to its close relationship with behavioral control, working memory (WM) is one of the cognitive processes most associated with CC. As WM and CC share the central executive (CE), it is believed that any understanding of the basic mechanisms of WM directly contributes to a greater understanding of more complex aspects of human cognition. To analyze the relationship between cognitive control capacity (CCC) and WM, 27 university students completed six tasks: backward majority function task-masked (MFT-M), digits (forward and backward), cubes (forward and backward), and three working memory complex span tasks (OSpan, RotSpan, and SymSpan) in two sessions. The correlation between CCC and WM tasks with a high CE component, specifically BD (backward digits), BC (backward cubes), and the three working memory complex span tasks, was only significant with the BC task. In contrast, WM tasks with a lower CE load, as expected, did not show statistically significant correlations with this capacity. The results obtained in this study do not demonstrate a relationship between CC and efficiency in solving WM tasks with a low central executive level. However, it is related to performance in tasks like BC, which have a higher central executive level; this suggests that greater CCC might somehow ensure that individuals perform well in such tasks. It is important to mention that the relationship between CC and various WM tasks is complex, and further studies are needed to clarify the contribution of CCC to the results obtained in WM evaluation tasks.

El control cognitivo (CC) es un proceso que coordina las operaciones mentales en condiciones de incertidumbre a niveles perceptuales o superiores controlando qué información llega a la conciencia para la toma de decisiones. Dada su estrecha relación con el control de la conducta, la memoria de trabajo (MT) es uno de los procesos cognitivos que más se han relacionado con el CC. Como la MT y el CC comparten al ejecutivo central (EC), se cree que cualquier comprensión de los mecanismos básicos de la MT conduce directamente a una mayor comprensión de aspectos más complejos de la cognición humana. Para analizar la relación entre capacidad de control cognitivo (CCC) y MT 27 estudiantes universitarios respondieron seis tareas: backward majority function task-masked (MFT-M), dígitos (progresión y regresión), cubos (progresión y regresión), y tres tareas de intervalo complejo de MT (OSpan, RotSpan y SymSpan) en dos sesiones. La correlación entre la CCC y las tareas de MT con un alto componente de EC: DR (dígitos en regresión), CR (cubos en regresión) y las tres tareas de intervalo complejo de MT únicamente fue significativa con la tarea CR. En cambio, las tareas de MT con una carga menor de EC, tal como se esperaba, no mostraron correlaciones estadísticamente significativas con esta capacidad. Los resultados obtenidos en este estudio no muestran una relación entre el CC y la eficiencia en la resolución de tareas de MT con bajo nivel de ejecutivo central. Sin embargo, sí se relacionó con el desempeño en tareas como CR cuyo nivel de ejecutivo central es más alto; esto implicaría que una mayor CCC de alguna forma podría garantizar que las personas tengan un buen desempeño en tareas de este tipo. Es importante mencionar que la relación entre la CC y las distintas tareas de MT es compleja y se requieren más estudios que permitan clarificar la contribución de la CCC en los resultados obtenidos en tareas que evalúan MT.
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/5; FP-M-2024-0162; Control cognitivo; Memoria de trabajo; Ejecutivo central; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18580